Autophagy: a double-edged sword in ischemia–reperfusion injury - Lingxuan Tang; Wangzheqi Zhang; Yan Liao; Weijie Wang; Xiaoming Deng; Changli Wang; Wenwen Shi (Cellular & Molecular Biology Letters)
Abstract Ischemia–reperfusion (I/R) injury describes the pathological process wherein tissue damage, initially caused by insufficient blood supply (ischemia), is exacerbated upon the restoration of blood flow (reperfusion). This phenomenon can lead to irreversible tissue damage and is commonly observed in contexts such as cardiac surgery and stroke, where blood supply is temporarily obstructed. During ischemic conditions, the anaerobic metabolism of tissues and organs results in compromised enzyme activity. Subsequent reperfusion exacerbates mitochondrial dysfunction, leading to increased oxidative stress and the accumulation of reactive oxygen species (ROS). This cascade ultimately triggers cell death through mechanisms such as autophagy and mitophagy. Autophagy constitutes a crucial catabolic mechanism within eukaryotic cells, facilitating the degradation and recycling of damaged, aged, or superfluous organelles and proteins via the lysosomal pathway. This process is essential for maintaining cellular homeostasis and adapting to diverse stress conditions. As a cellular self-degradation and clearance mechanism, autophagy exhibits a dualistic function: it can confer protection during the initial phases of cellular injury, yet potentially exacerbate damage in the later stages. This paper aims to elucidate the fundamental mechanisms of autophagy in I/R injury, highlighting its dual role in regulation and its effects on both organ-specific and systemic responses. By comprehending the dual mechanisms of autophagy and their implications for organ function, this study seeks to explore the potential for therapeutic interventions through the modulation of autophagy within clinical settings.